Isolation of Staphylococcus aureus from raw milk of cows at Salah Al -Din province and evaluation of their susceptibility to antibiotic: ¹ويثُى عهً سهطاٌ² و سهى ياهزعبذ ¹َهاد عبذ انحسٍٍ جعفز - جعفر, نهاد عبدالحسين (The Iraqi Journal of Veterinary Medicine, 2012)
The study was designed for isolation of Staphylococcus aureus from raw milk of cows at different regions of salah al-din province. A total number of 109 samples were collected form October (2010) to May (2011). The result of study showed that the number of isolates were (14) from (60) positive samples (82.22%). Antibiotic susceptibility test showed different results for susceptibility according to types of antibiotics that used in this study which include the followings: Amoxycillin, Ampicillin, Cefoxetine, Methcillin, Ciprofloxacin, Clavulinic acid and Erythromycin. The results showed that 50% of the isolates were susceptible for Methecillin, Cefoxetine, and Clavulanic acid-Amoxycillin), While Erythromycin was active against (79%) of the isolates, and Ampicillin was active against (57%), on the other hand, all isolates were susceptible to Ciprofloxacin which considered the most effective antibiotic against the bacteria in this study (100%).